(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Medieval literary works from South Asia hardly ascribe any space to women in their narratives. In recent writings however, there is a tendency to address this gap. The present essay studies the textual representations of Fatima bin Sam (d. between 1220-1230) in the table talks malfūzāt and a biography of Chishtī Saints of the 14th century and analyses the methods by which she is memorialized in the oral traditions at the Chishtī shrines (dargahs). The objective of this paper is to delve into the possible reasons and analyze the literary techniques and strategies through which she is remembered in the aforementioned traditions. The paper argues that the Chishti Shaikhs of the 13th and 14th century sanctified Fātima bin-Sām as a saint and role model through specific literary tropes and rhetorical devices to motivate and encourage other women to take to the mystic path.